Challenging the apartheids of knowledge in Higher Education through Social Innovation - McIntosh, Shona (Critical Studies in Teaching and Learning, 2023)
Joanna Bezerra, Craig Paterson & Sharli Paphitis (Eds.), Challenging the apartheids of knowledge in Higher Education through Social Innovation. Sun Press. Dr. Shona McIntosh, Department of Education, University of Bath.